Biologi Reproduksi Ikan Belida (Notopterus notopterus Pallas, 1769) di Kolong-Bendungan Simpur, Pulau Bangka - Andi Gustomi; . Sulistiono; . Yonvitner (Institut Pertanian Bogor, 2016)
The knowledge of fish reproduction is the most important in freshwater management continously. The research was done from February-July 2013, was aiming to describe information on reproductive aspects of belida fishes (Notopterus notopterus),i.e. sex ratio, gonado somatic stages, gonado somatic index, first size of maturity, fecundity, and spawning type. The fish Samples was taken by gill net which had many sizes such as 2, 2.5, 3, and 4 cm. Each gill net has length 30 m and width 2 m. Belida fishes have caught during research amounted 497 ind, which consisted of: 237 male and 260 female. Sex ratio male and female fish were relatively balance. The maturity gonad of male fish is faster than female fish. Featherback do spawn every month for each observation during the research. The spawning type of Featherback is partial pattern (step by step). The first size of maturity gonad from male fish was in length 135 mm and female fish was in length 162 mm. Fecundity of Featherback was in range 1.051-6.057 eggs. Fecundity is not influenced by length or weight body. For the sake to keep Featherback population needed a regulation, such as: the mesh size regulation of gillnet have to 30 mm or equal with 1.5 inci.